Politik Kewargaan: Upaya Nelayan Perempuan dalam Memperoleh Keadilan (Studi Pada Desa Purworejo, Kabupaten Demak) - Rajendra Walad Jihad; Yuwanto Yuwanto; Nunik Retno Herawati (Jurnal Ilmu Sosial dan Ilmu Politik)
The efforts of fisher women in Purworejo Village to obtain justice are within the scope of the concept of civic politics. For dozens to decades, fisher women in Purworejo Village have been going to sea without obtaining legality regarding their employment status on their KTP. The aim of this research is to study the various disparities experienced by fisher women in Purworejo Village, the efforts made to achieve justice, and the effects realized from these efforts to achieve justice. Qualitative and descriptive are the methods and approaches used in this research. Secondary and primary data resulting from participant observation, in-depth interviews, and documentation are the data sources for this research. Meanwhile, the researcher uses Kristian Stokke's political theory of citizenship as a theoretical framework to strengthen the analysis in this research. The results of this research found that there are two forms of inequality experienced by fisher women in Purworejo Village, namely social inequality and rights inequality. Efforts to resolve this injustice include identification and education, advocacy for the transition of employment status on KTPs, and monitoring the realization of rights for fisher women. The effect obtained from these efforts is the handling of various social inequalities and gaps in rights faced by fisher women in Purworejo Village.